2004
DOI: 10.1007/s00223-004-0240-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Osteopenia and Lumbar Intervertebral Disc Degeneration in Ovariectomized Rats

Abstract: Ovariectomy (OVX) can cause bone loss in rats, but little is known about how it also induces lumbar intervertebral disc degeneration (LVD). This study investigated how estrogen deficiency affected intervertebral discs in OVX rats. Thirty 3-month-old female Sprague-Dawley rats were divided randomly into three equal groups. The baseline control group (BL) was killed at the beginning of the experiment. An ovariectomy was performed in 10 rats (OVX group) and another group of 10 rats was subjected to a sham surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 32 publications
2
41
0
1
Order By: Relevance
“…Manson et al [17] reported that although disc degenerative changes are observed in both sexes, women seem to be more susceptible to instability, malalignment, and structural deterioration. Recently, it was reported that ovariectomy can induce intervertebral disc degeneration in female rats [10]. Untreated postmenopausal women have reduced total lumbar disc height compared to postmenopausal women treated with hormone replacement therapy [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manson et al [17] reported that although disc degenerative changes are observed in both sexes, women seem to be more susceptible to instability, malalignment, and structural deterioration. Recently, it was reported that ovariectomy can induce intervertebral disc degeneration in female rats [10]. Untreated postmenopausal women have reduced total lumbar disc height compared to postmenopausal women treated with hormone replacement therapy [18].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that osteoporosis may be an etiological factor in the development of lumbar disc degeneration with osteoporosis inducing loss of vertebral height, leading to instability, facet arthrosis, and disc degeneration [9]. In an experimental setting, it has been shown that, together with vertebral osteoporosis, ovariectomized female rats develop lumbar disc degeneration [10].…”
Section: Introductionmentioning
confidence: 99%
“…Degenerative changes in the intervertebral disks were observed and the degrees of change in the stained sections were scored independently by three individuals blinded to the experimental protocol, using the disk degeneration assessment scoring system (Table 1) described by Wang et al [7].…”
Section: Experimental Designmentioning
confidence: 99%
“…Relative estrogen deficiency may contribute to accelerated disk degeneration in postmenopausal females [6]. In addition, our previous studies have revealed a strong association between osteopenia and disk degeneration in OVX rats, and intervention by alendronate, a widely accepted antiresorptive agent, could not only prevent osteopenia but also inhibit intervertebral disk degeneration [7,8].…”
Section: Introductionmentioning
confidence: 98%
“…Imada et al ( 13 ) reported that the incidence of degenerative lumbar spondylolisthesis was about three times higher in women with a history of ovariectomy, compared with age-matched control subjects who did not undergo ovariectomy. Female rats have an increased tendency to develop intervertebral disk degeneration after undergoing ovariectomy ( 14 ), and estrogen supplementation can halt the development of this ovariectomy-associated disk degeneration (Wang YX et al, unpublished data, 2010). Estrogen, which has a variety of biologic effects, also seems to infl uence disk degeneration.…”
mentioning
confidence: 99%